Iyanu : child of wonder. Volume 4 - Okupe, Roye (Iyanu: Child of Wonder, 2025)
"Iyanu must face her destiny and save all of Yorubaland! She has help from her friends: Biyi, a carefree adventurer; Toye, the bookworm; and Ekun, the magical and opinionated giant leopard! Together, all four--also known as Team Chosen--embark on an epic adventure full of twists, turns, and laughs that will change their lives forever!"--Rear cover.